Interpretasi Sufistik Atas Teks Al-Qur'an : Memahami Analisis Nadzari dan Isyari - AHMAD KHAMID (Al Irfani: Journal of Al Qur'anic and Tafsir, 2020)
Al-Qur'an interpretation thoughts are born of Islamic intellectuals, one of whom is the Sufi scholars. The development of the teachings of tasawwuf Articles give a role to the development of interpretation among Sufis. This article uses exploratory analysis, examining the analytical patterns of the interpretation of the Qur'an carried out by two Sufi schools, Sufi Nadzari and Sufi Isyari. The emergence of Sufistic interpretation develops from the Sufism tradition performed by the Salik in religious. Sufi nadzari's interpretation is built on the basis of knowledge, whereas Sufi isyari's interpretation is based on the sincerity of a Sufi's Second, in the Sufi nadzari's interpretation a Sufi understands that all verses of the Koran have distinctive meanings, whereas Sufi Isyari's interpretation uses the basic assumption that a Sufi verse The Qur'an has an inner meaning "Sufi Nadzari understands the Qur'an by combining inner and rational contemplation. Sufi Isyari understands al-Qur'an by way of mujahadataunnafs, a heart that istiqomah will be able to permeate ma'ani, cues, lata'if al-Qur'an”.